Ethics for "intelligent" beings created by man: scenarios of the future - Mijartovic, Zorica; Jašić, Orhan (Epistēmēs Metron Logos, 2021)
Artificial intelligence is a challenge for many scientists and researchers today. On the one hand, the development of artificial intelligence can be beneficial for people as it can significantly facilitate their daily lives and jobs. On the other hand, there is the fear that we will not succeed in developing "friendly artificial intelligence" and that these created intelligent beings becoming autonomous persons will bring many problems. Worries go so far as to assume that artificial intelligence will displace humans and take their place in all spheres of life. In this article, we have tried to present future scenarios concerning the development of artificial intelligence and indicate how necessary it is to have ethics in this discourse. Keywords: Artificial Intelligence, Algorithms, Bioethics, Ethics, Software, Science Fiction, Technology.